Gatherings in Uzbek Mourning Ceremonies - Payziyeva Mukaddas Khabibullaevna (Researchparks Publishing, 2022)
The article is devoted to mourning rites of Uzbeks; on the basis of field ethnographic and scientific literature the originality of mourning among the Uzbeks of Tashkent city is revealed.